2022
DOI: 10.21203/rs.3.rs-956340/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The undergraduate experience of the transition of the obstetrics and gynaecology programme to blended learning in response to the COVID-19 pandemic

Abstract: Background: The Covid 19 pandemic radically changed our lives worldwide in 2020. Control of the pandemic required public health interventions which included social distancing and the minimising social gatherings. The implementation of these measures resulted in major changes in the delivery of healthcare education.Aim: This observational study reports on the undergraduate experience of the transition of the obstetrics and gynaecology programme from a traditional face-to-face approach to a blended learning prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Ob/Gyn clerkship durations ranged from 4 weeks 40 to 11 weeks 18 and were block rather than longitudinal placements. Publications also described teaching delivered during Ob/Gyn clerkships, within hospitals as opposed to primary care, general practitioner, or family medicine practices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ob/Gyn clerkship durations ranged from 4 weeks 40 to 11 weeks 18 and were block rather than longitudinal placements. Publications also described teaching delivered during Ob/Gyn clerkships, within hospitals as opposed to primary care, general practitioner, or family medicine practices.…”
Section: Resultsmentioning
confidence: 99%
“…The recommendations identified in our study could assist medical school course leaders in Ob/Gyn to plan and bench mark their curricula. The overarching themes included teaching on antenatal care, with the recent COVID-19 pandemic and more online teaching 5,40 ;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the findings in this study, multiple authors have reported on the positive and negative experiences with online and blended learning since the COVID-19 pandemic (Connolly & Abdalla 2022 :1; Gordon et al 2020 :1; Rafi et al 2022 :1; Saber et al 2022 :1). This has resulted in the publication of, among others, guidelines for developing blended curricula in medical education (Rafi et al 2022 :1), best practice examples of moving healthcare education from traditional face-to-face teaching to blended learning (Tuthill, et al 2022 :1–11), and the dissemination of research on the challenges and barriers of blended learning in healthcare education (Saber, et al 2022 :8). From the university where this study was conducted, limited documentation on online and blended learning has been published, even though several blended learning practices have continued beyond the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%